ANALISIS INOVASI PENERAPAN STRATEGI PEMBELAJARAN FIQIH - Wahidin (JURNAL PENDIDIKAN DAN KEGURUAN, 2026)
This study aims to analyze innovations in the implementation of Fiqh learning strategies in Islamic educational institutions. In the context of Fiqh education, adapting teaching approaches to social and cultural dynamics is essential to ensure that students can understand and apply Islamic teachings in a relevant manner. The method used in this study is a qualitative approach with a case study design focused on a State Islamic Junior High School (Madrasah Tsanawiyah Negeri) in Kapuas Regency. The informants in this study consisted of one principal, five Fiqh teachers, and twenty students. Data were collected through interviews, observations, and documentation. The data collection techniques involved interviews with teachers, students, and the principal to explore their perspectives on the implementation of Fiqh learning strategies. Classroom observations were conducted to analyze interactions between teachers and students as well as the methods used. In addition, relevant documents such as lesson plans, syllabi, and teaching materials were also collected. Data obtained from interviews and observations were analyzed using thematic analysis methods, including interview transcription, identification of key themes, and data coding. Conclusions were drawn based on the themes identified. The results of the study indicate that Fiqh learning integrated with technology, such as digital media and online learning platforms, has a positive impact on student engagement. Project-based strategies and group discussions are effective in enhancing interaction between students and teachers, as well as helping students understand Fiqh material in a more practical context. The implementation of formative assessment and continuous evaluation has been proven to significantly improve students’ understanding. The findings highlight the use of applications and e-learning platforms in Fiqh learning, as well as the application of project-based and discussion methods as effective strategies. This study also recommends continuous professional development for teachers, improvement of infrastructure such as internet access and technological devices, and the development of adaptive content relevant to contemporary issues to make Fiqh learning more engaging for students. A collaborative environment that supports interaction between students and teachers needs to be facilitated, while continuous evaluation, including technology-based formative assessment, should be optimized to provide fast and accurate feedback, thereby encouraging continuous improvement in the learning process.